PENINGKATAN HASIL BELAJAR SISWA TENTANG PENGOLAHAN DATA MELALUI MODEL TALKING STICK - Noviyanti M. (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2020)
This study entitled "improving student learning about the results of processing of Data Through the Model of the Talking Stick".The problem in this research is "How does the Talking Stick learning model can improve the learning results of students in learning mathematics?".The purpose of this research is to find out how the learning model talking stick can improve student learning outcomes.As well as your long-term goal is this model can motivate students in learning and improving the results of his studies.This research uses research class. The method used is a Model of the Talking Stick.Its population is a whole grade VI SDN 51 Lubuklinggau Year Lesson 2018/2019 of 27 students.Data collection techniques to techniques and tests can be concluded that the results of the study on the Data processing through the model of the Talking Stick can be increased.